A Spatial Analysis of Cultural Ecosystem Service Valuation by Regional Stakeholders in Florida—A Coastal Application of the Social Values for Ecosystem Services (SolVES) Tool - Alisa W. Coffin; Robert A. Swett; Zachary D. Cole (EDIS)
How can we measure how Sarasota Bay residents value their area’s cultural ecosystem services? This 4-page fact sheet describes a project to use a geographic information system application, SolVES 2.0, to assess, map and quantify environmental benefits to people to assist in coastal development decision making. Written by Alisa Cofin, Robert Swett, and Zachary Cole, and published by the UF Department of Sea Grant, November 2012.